1965
DOI: 10.2134/agronj1965.00021962005700060025x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Level and Osmotic Pressure of the Nutrient Solution on Incidence of Puccinia graminis and Helminthosporium sativum Infection in Merion Kentucky Bluegrass1

Abstract: Synopsis Merion bluegrass grown in solution culture produced lower yields of foliage under low levels of nitrogen and high levels of osmotic pressure than when treated with high nitrogen and low osmotic pressures. Turf was resistant to inoculation with Puccinia graminis Pers. at all treatment combinations. Numbers of Helminthosporium sativum Pammel, King, and Bakke lesions per leaf blade and average size of lesions increased with increasing levels of nitrogen and decreasing osmotic pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1969
1969
1992
1992

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Ophiobolus patch was reported to be more severe on seedling turf grown at high nitrogen levels, but on mature, established turf the reverse was true (14). Cheesman (7) reported that increasing nitrogen increased both the number of Helminthosporium lesions and their size on bluegrass foliage.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Ophiobolus patch was reported to be more severe on seedling turf grown at high nitrogen levels, but on mature, established turf the reverse was true (14). Cheesman (7) reported that increasing nitrogen increased both the number of Helminthosporium lesions and their size on bluegrass foliage.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Shoem. causes a leaf spot of Poa prcltensis L. that is influenced by numerous cultural and environmental factors, including nitrogen fertilization (Cheesman et al 1965;Robinson and Hodges 1977), mowing height (Drechsler 1930;Halisky et al 1966), temperature (Hodges and Madsen 1978), light quality and photoperiod (Nilsen et al 1979), and postemergence herbicides (Hodges 1978;Madsen and Hodges 1983b). Many of the herbicides used to control weeds in turf of P. pratensis have the potential for increasing the severity of leaf spot (Hodges 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Hoagland and Arnon (13) stated that these experiments have led to the determination of the chemical elements essential for plant life, thereby profoundly influencing the practice of soil management and fertilization for purposes of crop production. While these techniques have been developed primarily for agronomic and horticultural crops they have been modified by Roberts (30) and others (7,25,31) for use with turfgrasses where the objective was to establish a community of plants competing for light, air and nutrients in a manner similar to soil culture. Troughton (36) noted that growth responses of grass plants in close association with one another differed from those plants cultured individually or widely spaced when both were subjected to clipping practices.…”
Section: Review Of Literaturementioning
confidence: 99%
“…This report pointed out the following nine factors as having a bearing on sodium chloride injury: (1) Amount of sodium chloride applied to roads, (2) Amount of sodium chloride reaching vegetation, (J) Water availability, (4) Temperature, (5) Wind, (6) Soil characteristics, (7) Plant dormancy, (8) Plant tolerance, (9) CUmulative effect •…”
Section: Sodium Chloridementioning
confidence: 99%